The Application of the Ijbari Principle in Islamic Inheritance Law - Riska Siti Alida; Ani Yumarni; Hidayat Rumatiga; Saddam Husein; Nova Monaya (DE'RECHTSSTAAT, 2025)
The principle of ijbari in Islamic inheritance law reflects the obligatory nature of the distribution of inheritance, which is determined directly by the decree of Allah SWT as stated in the Qur'an and Hadith. This principle ensures that inheritance rights are granted automatically and cannot be changed by anyone, this is to maintain justice and avoid disputes between heirs. The ijbari principle also emphasizes that inheritance law is absolute and must be implemented in accordance with sharia guidelines. This study aims to analyze the application of the ijbari principle in Islamic inheritance law by reviewing its legal basis, distribution mechanism, and role in maintaining family harmony and social justice. This research also seeks to clarify how this principle functions in sharia, while highlighting its significance in achieving justice and equality in the distribution of inheritance. This study uses a normative juridical research method, with a legal approach, laws and regulations and other sources used as data sources related to research that provide an understanding of how the ijbari principle  is applied in practice. This research shows that the ijbari principle plays an important role in ensuring the automatic and fair distribution of inheritance rights, which is the key to maintaining justice and preventing conflicts. The study also highlights that this principle not only protects the rights of heirs, but also reinforces Islam's core values of equality and justice.